Advancements in Big Data Analytics: A Comprehensive Review of Tools and Technologies, from Hadoop to Spark - Ravichandran, Prabu (Journal of Science & Technology, 2020)
This research paper provides a comprehensive review of advancements in big data analytics, focusing on the evolution of tools and technologies from Hadoop to Spark. Big data analytics has revolutionized the way organizations process, analyze, and derive insights from massive volumes of data. The emergence of distributed computing frameworks such as Hadoop and Spark has played a pivotal role in enabling efficient processing of large-scale datasets. This paper examines the key features, functionalities, and comparative advantages of these frameworks, along with exploring other relevant tools and technologies in the realm of big data analytics. By synthesizing current research findings and industry practices, this paper aims to offer insights into the landscape of big data analytics tools and technologies, facilitating informed decision-making for organizations seeking to leverage the power of big data.